Perubahan Kurikulum Pendidikan Agama Kristen Berdampak Pada Strategi Guru Dalam Mengajar Di Sekolah - Rismag Dalena Florentina Monica Br Manurung; Talizaro Tafonao (Jurnal Apokalupsis, 2021)
The purpose of writing this article is to find out the impact experienced by teachers in curriculum changes and find the right strategy to be applied to students. In this paper, there are teachers who are not ready and less enthusiastic in improving their competence so that they find the right strategy to teach students. The method used is a qualitative research method by examining the extent to which changes in the Christian religious education curriculum have an impact on teachers' strategies in teaching in schools. In the analysis process, the author uses various sources of literature as references such as books, journals and interviews to support the author's analysis. The results found by the author are related to the teacher's strategy in dealing with curriculum changes, namely by increasing their competence through training (Worksop), classroom action research, following the times, and conducting discussions with colleagues as explained in this article. Thus teachers are able to teach in schools with the right strategy even in the midst of curriculum changes that occur.